Research methods - Dane, Francis C. (Pacific Grove, California : Brooks/Cole Publishing Company, 1990)
This chapter is an introduction to research. Like most introductions, it is a broad overview of what's to come. Admittedly, it is also an attempt to pique your interest.
Part One. The nature of research -- Part Two. Design -- Part Three. Resource chapters.
Includes bibliographical references and index.
Keywords: SOCIAL SCIENCE